2019
DOI: 10.1038/s41413-019-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte dysfunction promotes osteoarthritis through MMP13-dependent suppression of subchondral bone homeostasis

Abstract: Osteoarthritis (OA), long considered a primary disorder of articular cartilage, is commonly associated with subchondral bone sclerosis. However, the cellular mechanisms responsible for changes to subchondral bone in OA, and the extent to which these changes are drivers of or a secondary reaction to cartilage degeneration, remain unclear. In knee joints from human patients with end-stage OA, we found evidence of profound defects in osteocyte function. Suppression of osteocyte perilacunar/canalicular remodeling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 85 publications
1
101
0
Order By: Relevance
“…[8,9] Osteocytes detect increased fluid flow in subchondral bone and then secrete signaling molecules that affect chondrocyte, osteoblast, and osteoclast activities that further contribute to osteochondral degeneration. [1,2,[10][11][12][13] A 3D in vitro model that recapitulates the strain and fluid flow of the osteochondral unit would enable key questions to be answered about the osteocyte's role in regulating osteochondral homeostasis and degeneration.…”
Section: Doi: 101002/adhm202001226mentioning
confidence: 99%
“…[8,9] Osteocytes detect increased fluid flow in subchondral bone and then secrete signaling molecules that affect chondrocyte, osteoblast, and osteoclast activities that further contribute to osteochondral degeneration. [1,2,[10][11][12][13] A 3D in vitro model that recapitulates the strain and fluid flow of the osteochondral unit would enable key questions to be answered about the osteocyte's role in regulating osteochondral homeostasis and degeneration.…”
Section: Doi: 101002/adhm202001226mentioning
confidence: 99%
“…However, treatments targeting only the signaling mechanisms responsible for AC degeneration may be insufficient to halt disease progression (7,(12)(13)(14). Recent evidence suggests that pathological alterations in subchondral bone also contribute to osteoarthritis development (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…OA is the most common type of arthritis with in ammatory disease in the synovial joints (32,33) . It is characterized by gradual degeneration of articular cartilage and changes in the structure and function of the entire joint (34,35) . In recent years, it has been reported that the canonical SMAD signaling of the TGF-β signaling pathway contribute signi cantly to cartilage maintenance and repair.…”
Section: Discussionmentioning
confidence: 99%